Labour Costs on the Vegetables: A Research on the location effect on salaries in Jiangsu Province, China - Huimin Zhang; Yancheng Liu; Zhiping Zhang; Minmin Miao (Ciência Rural, 2021)
ABSTRACT: In this study, the labour requirement and labour cost of common vegetable cultivation were investigated to help agricultural enterprises and family farms establishing reasonable “working hour” management systems in Jiangsu Province. The labour requirement of each step of three type of producers, agriculture enterprises, family farms, and private vegetable growers, in three regions in Jiangsu Province, named north, middle and south Jiangsu, was investigated by on-site observation or questionnaire survey during 2018 and 2019. The labour cost of each step and each vegetable was counted according to the labour requirement and the salary level. The results indicated that “residue cleaning”, “soil preparation and bedding”, “plant regulation”, “auxin treatment of tomato flowers” and “hand pollination” accounted for higher proportions of labour cost amongst the entire vegetable culture process. No significant differences in the labour requirements of the investigated vegetables were reported amongst three regions in Jiangsu Province. However, the order of labour cost is south Jiangsu > north Jiangsu > middle Jiangsu, due to the salary difference amongst three regions. Watermelon, broccoli and chive are more suitable for growing by agricultural enterprises since they have relatively low unit labour and high prices. We established a method to calculate and analyze labour requirement and cost of vegetable production in Jiangsu Province, which also may be instructive for other regions. In addition, our results provided useful data for various vegetable producers to improve their labour management.